2005
DOI: 10.1261/rna.7190705
|View full text |Cite
|
Sign up to set email alerts
|

NMR structure of the apoB mRNA stem–loop and its interaction with the C to U editing APOBEC1 complementary factor

Abstract: We have solved the NMR structure of the 31-nucleotide (nt) apoB mRNA stem-loop, a substrate of the cytidine deaminase APOBEC1. We found that the edited base located at the 5 end of the octa-loop is stacked between two adenosines in both the unedited (cytidine 6666) and the edited (uridine 6666) forms and that the rest of the loop is unstructured. The 11-nt "mooring" sequence essential for editing is partially flexible although it is mostly in the stem of the RNA. The octa-loop and the internal loop in the midd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(49 citation statements)
references
References 53 publications
3
45
0
1
Order By: Relevance
“…These data suggest that site 6666 has greater accessibility/affinity to the editing complex compared to other sites. This is consistent with the mooring sequence being near site 6666 and the mooringlike sequence being near site 6802 and the proposal that canonical editing by the editing complex is associated with mooring motif recognition (Hersberger and Innerarity 1998;Maris et al 2005).…”
Section: Core Editing Cofactor Acf Increases Apobec-1 Hypermutationsupporting
confidence: 87%
See 1 more Smart Citation
“…These data suggest that site 6666 has greater accessibility/affinity to the editing complex compared to other sites. This is consistent with the mooring sequence being near site 6666 and the mooringlike sequence being near site 6802 and the proposal that canonical editing by the editing complex is associated with mooring motif recognition (Hersberger and Innerarity 1998;Maris et al 2005).…”
Section: Core Editing Cofactor Acf Increases Apobec-1 Hypermutationsupporting
confidence: 87%
“…ACF and APOBEC-1 form a complex minimally required for in vitro apoB mRNA editing. It has been proposed that ACF first recognizes the flexible nucleotides of the apoB mRNA mooring sequence and subsequently melts the stem-loop, exposing the amino group of cytidine 6666 to APOBEC-1 (Maris et al 2005). ACF also lowers the temperature requirement to promote a conformational transition in the RNA substrate (Chester et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…ACF is the RNA binding component of the apoB RNA editing enzyme and functions both to bind an AU-rich region of the nuclear apoB transcript and also to anchor and position the dimeric RNA-specific cytidine deaminase Apobec-1 into an optimal configuration for C to U deamination of the targeted base at position 6666 (4,(23)(24)(25). Structural studies using nuclear magnetic resonance demonstrated that ACF exhibited greater binding affinity for apoB than did Apobec-1 and suggested that increasing concentrations of ACF restricts the RNA binding of Apobec-1 and promotes site-specific C to U editing (25).…”
Section: Discussionmentioning
confidence: 99%
“…This fragment has been considered the minimal stem-loop recognized by the editosome. 29,55 However, this construct resulted completely uneditable in our system (data not shown), possibly due to secondary/tertiary structures in the transcript that masked the editing site.…”
Section: Resultsmentioning
confidence: 85%
“…Thus APOBEC1 Complementation Factor (ACF) is required for the specificity of the targeting through its interaction with the mooring sequence. [24][25][26][27][28][29][30] Another molecule, RBM47, has been recently shown to be sufficient for the APOBEC1-mediated RNA editing. 31 Other molecules, GRY-RBP and hnRNP-C1 among them, have been characterized as negative regulators of the editing process.…”
Section: Introductionmentioning
confidence: 99%